Yam production in the derived coastal savanna zone of Ghana Past, Present and Future Prospects - Otoo, E.; Asiedu, Robert; Ennin, S.; Ekpe, E. (2005)
‘Bodwease’, a yam-producing area in the Efutu-Awutu-senya district of Ghana, is touted as a ‘romantic town’ due to several development initiatives being implemented by the government of Ghana in the area, amongst them the president special initiatives(PSI) on cassava processing for starch. The area has unique characteristics that serve as a magnet attracting several local and foreign investors, as well as private investors and non-governmental ( not-for –profit) organizations. It is very close (56km) to Accra, the capital, and lies between two major markets of Kasoa and Mankessim. It has unique climatic and soil characteristic making the area ideal for growing of pineapples (number 0ne non- traditional export crop in Ghana), yams ( second most important non-traditional export crop) cassava and maize. It also has a long history of producing yams of high quality and has some unique yam varieties found only in that area in Ghana. Yam production constraint and methods there are also unique, but production level have been declining in recent times. This paper examines past and present yam production in the area. It also compares the economics of yam production in the derived coastal savannah zone of Ghana to that in the forest/savannah transition and the forest zones. The future prospects for yam production in the ‘Bodwease’ area are discussed and measures to mitigate the challenges to this enterprise are recommended.